How Social Isolation Affects Disaster Preparedness and Response in Australia: Implications for Social Work. Issue 4 (2nd October 2018) - Howard, Amanda; Agllias, Kylie; Bevis, Miriam; Blakemore, Tamara
ABSTRACT: Natural disaster impacts on populations already experiencing significant health, income, and social disadvantage, are both more intense and longer lasting than for the general population. The intersection of social isolation and poverty for some groups often results in significant risks during the immediate crisis of a disaster and ongoing challenges for recovery. This article reports on qualitative research examining natural disaster preparedness with five "at-risk" populations in regional Australia. The research was undertaken as part of a project sponsored by a regional organisation of local councils in New South Wales to map and understand spatial and social factors shaping natural disaster risks and responses. Seventeen focus groups were held with 111 participants; older people, people with disabilities, families with children under five, low-income households, and people from culturally and linguistically diverse (CALD) backgrounds. Findings illuminated participant experiences of the intersection between sociogeographic disadvantage with social isolation in the context of natural disaster preparation and response. IMPLICATIONS Social isolation—or the intersection of social and geographic disadvantage—appears to be a complex contributor to vulnerability in disaster preparation and response. Disaster risk needs to be assessed as part of social work support for vulnerable people.